A randomized controlled trial comparing scalable weight loss treatments in primary care. (9th October 2014) - Barnes, Rachel D.; White, Marney A.; Martino, Steve; Grilo, Carlos M.
<x xml:space="preserve">Abstract</x> Objective Primary‐care (PC) settings may be an opportune place to deliver obesity interventions. Scalable interventions utilizing motivational interviewing (MI), supported by Internet resources, may overcome obstacles to effective obesity treatment dissemination. This study was a randomized controlled trial testing two Web‐supported interventions, motivational interviewing (MIC) and nutrition psychoeducation (NPC), an attention‐control intervention, in comparison with usual care (UC). Methods Eighty‐nine overweight/obese patients, with and without binge eating disorder (BED), were randomly assigned to MIC, NPC, or UC for 3 months in PC. Patients were assessed independently at post‐treatment and at 3‐month follow‐up. Results Weight, triglyceride levels, and depression scores decreased significantly in NPC when compared to UC but not MIC; UC and MIC did not differ significantly. Weight loss results maintained at 3‐month follow‐up: approximately 25% MIC and NPC patients achieved at least 5% weight loss which did not differ by BED status. Fidelity ratings were high and treatment adherence was associated with weight loss. Conclusions This is the first randomized controlled trial in PC testing MI for weight loss to include an attention‐control intervention (NPC). NPC, but not MIC, showed a consistent pattern of superior benefits relative to UC. BED status was not associated, but treatment adherence was associated, with weight loss outcomes.